2013
DOI: 10.3928/00220124-20130916-79
|View full text |Cite
|
Sign up to set email alerts
|

Concept Mapping in a Critical Care Orientation Program: A Pilot Study to Develop Critical Thinking and Decision-Making Skills in Novice Nurses

Abstract: Concept maps are an effective tool for educators to use in assisting novice nurses to develop their critical thinking and clinical decision-making skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 19 publications
1
10
0
1
Order By: Relevance
“…In addition to Buntting et al (2006) [52] who said that in their study about 33% of the students also identified that concept mapping helped them to identify relationships between concepts. Also Senita (2008) [17] said that in her research, a survey of nursing students at Kent State University, Ashtabula Campus, revealed that nursing students found concept mapping useful to their learning in the clinical setting and Wahl & Thompson (2013) [53] said that in their research nursing students feeling satisfied and experiencing positive attitude toward clinical simulation and scenarios after utilizing concept maps in their clinical training.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Buntting et al (2006) [52] who said that in their study about 33% of the students also identified that concept mapping helped them to identify relationships between concepts. Also Senita (2008) [17] said that in her research, a survey of nursing students at Kent State University, Ashtabula Campus, revealed that nursing students found concept mapping useful to their learning in the clinical setting and Wahl & Thompson (2013) [53] said that in their research nursing students feeling satisfied and experiencing positive attitude toward clinical simulation and scenarios after utilizing concept maps in their clinical training.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 The results of a study also found that novice nurses could manage to promote their critical thinking by employing CM. 25 Therefore, the necessity of using critical thinking skills in the nursing profession in order to improve the quality of nursing care must be stressed. 26 Other findings of the study suggest that use of CM helps facilities the provision of patient-centered care by reducing the complexity of theoretical lessons, creating interest towards the clinical environment and increasing motivation in students.…”
Section: Discussionmentioning
confidence: 99%
“…A robust literature supports the use of certain educational interventions in advancing CT. 5,[17][18][19][20] Additional findings of systematic reviews have suggested that development of CT is enhanced when the teaching strategies are explicit and use higher-order questions. However, the findings remain equivocal regarding instructional approaches and teacher or student characteristics.…”
Section: Resultsmentioning
confidence: 99%